STRUKTUR DAN KOMPOSISI VEGETASI DI AREAL PETAK UKUR PERMANEN (PUP) PT. KAWEDAR WOOD INDUSTRY KABUPATEN KAPUAS HULU - Andewi, Bibiana Ating; hanuddin, Bur; Dewantara, Iswan (Universitas Tanjungpura, 2015)
This study aims to determine the structure and composition of the vegetation in the area of permanent sample plots (PSPs) PT. Kawedar Kapuas Hulu. The benefit of this study is expected to be a reference in the PUP area management efforts in the future. The research was conducted in the area of permanent sample plots (PSPs) PT. Kawedar Wood Industry Kapuas Hulu for 4-week study effectively in the field. The method in this study is a terraced-line method which is a combination of to track and double plot, which placed intentionally (purposive sampling). Transect made of four (4) lanes in the direction of the wind, which is the aspect of the East, West, South, and North, with the width of each lane 20 meters long and Â± 500. The results of the research are 48 species that include: 36 species of trees with 745 individuals, 37 species of poles with 904 individuals, 29 species of saplings with 1.266 individuals, 30 species of seedlings with 1.960 individuals. Diversity of trees (H Ì…) 1.2604, poles (H Ì…) 1.1537, saplings (H Ì…) 1.2094 and seedling (H Ì…) 1.3141. This suggests that the species diversity index value stands at PUP area. PT. Kawedar Wood Industry is the diversity of the medium, which ranged from 1.5 to 3.5. Keyword: Structure and composition, permanent sample plots, vegetation